Efficacy and Mechanisms of Silybum Marianum, Silymarin, and Silibinin on Rheumatoid Arthritis and Osteoarthritis Symptoms: A Systematic Review - Habibi Ghahfarrokhi, Shahrzad; Heidari-Soureshjani, Saeid; Sherwin, Catherine M.; Azadegan-Dehkordi, Zahra (Current Rheumatology Reviews, 2024)
Background: Rheumatoid arthritis (RA) and osteoarthritis (OA) are the most common forms of skeletal disease worldwide. Objective: The current systematic review investigated the mechanisms of Silybum marianum, silymarin, and silibinin on RA and OA symptoms. Methods: The PRISMA 2020 statement was used for reporting Items in this systematic review. The result was a list of five databases, including Web of Science, Cochrane Library, Embase, PubMed, and Scopus. After determining the inclusion and exclusion criteria, of 437 records identified, 21 studies were eligible. The data were extracted from the studies and imported into an Excel form, and finally, the effects, outcomes, and associated mechanisms were surveyed. Results: Silybum marianum and its main constituents revealed immunomodulatory, anti-inflammatory, antioxidant, and anti-apoptotic properties in humans and laboratory animals. Moreover, they protect the joints against the cartilage matrix's hypocellularity and fibrillation, reduce synovitis, and inhibit degeneration of aggrecan and collagen-II in human chondrocytes. They also, through reducing inflammatory cytokines, show an analgesic effect. Although silymarin and silibinin have low absorption, their bioavailability can be increased with nanoparticles. Conclusion: In experimental studies, Silybum marianum, silymarin, and silibinin revealed promising effects on RA and OA symptoms. However, more clinical studies are needed in this field to obtain reliable results and clinical administration of these compounds.
Keywords: rheumatoid arthritis